Determinants of Import Demand of Rice in Uganda - Hyuha, T.S.; Ekere, William; Bantebya Kyomuhendo, Grace (International Journal of Applied and Pure Science and Agriculture (IJAPSA), 2017)
Rice has been singled out as one of the crops that play an important role as both food and a cash crop in Uganda. Its importance has become more critical due to increasing demand. The increased demand has created a gap in domestic supply which has to be covered through imports. This study analyses determinants of import demand for rice in Uganda using econometric methods. Population, domestic rice production, own price and own consumption were found to be significant and therefore influencing rice imports in Uganda. Thus there is a need to increase supply through supporting farmers to increase domestic rice production to stabilize prices, If the country is to be self sufficient in rice as a way of saving foreign exchange, it would have to control its high population growth rate or increase domestic production through adopting high yield increasing technologies.
Keywords: Uganda; Rice; Import demand